ANALISIS PERAN RETRIBUSI TRANSPORTASI DARAT TERHADAP PEREKONOMIAN DI KABUPATEN POSO - Hengkeng, Join (Katalogis, 2015)
This study aims to determine how the role of land transport sector retribution in the economy of Poso Regency and how to influence land transport modes on the economy in the district of Poso. This type of research is categorised as qualitative descriptive analysis techniques, The results show that a). The role of land transport sector: (1) Regional revenue increase, it will affect the level of regional income. Land transportation sector levy is one of the ability of region to implement autonomy in terms of regional financial capability (2). Increase economic growth, withdrawal rate, taxes, and other costs that exist in the road transport sector in order to accelerate the economic growth in Poso Regency. Vehicle Test levy, Terminal Business service levies, Port Business Services levy, Route Permit Levy, Road Closure levy are the important source of income for the region to be improved. The other roles in the land transport sector include: 1). Availability of goods, 2). Stability and match, 4). Increase the value of land, 5). Development of small scale enterprises. 6). The occurrence of urbanization and population density. 7). Reduce poverty.